THE ESSENCE AND FUNCTIONAL CHARACTERISTICS OF THE “ANTICIPATORY COMPETENCE” PHENOMENON WITHIN MODERN HIGHER EDUCATION PARADIGMS - F.M. Sadriddinova (International Journal of Literature and Language Studies, 2026)
The article provides a systematic analysis of the essence and functional characteristics of the anticipatory competence phenomenon within the modern higher education paradigm. It delineates the structural levels of this competence and highlights its crucial functions in shaping students' proactive thinking. Furthermore, practical recommendations are offered for integrating Foresight sessions and simulators into the educational process to foster future intelligence.